Program Kemitraan Masyarakat: Perancangan Praktikum Matematika dan IPA Sederhana bagi Guru SMP - Kadek Ayu Astiti; Andam S. Ardan; Damianus Dao Samo (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2021)
This community service activity improves teacher skills in carrying out simple Mathematics and Natural Sciences practical activities. This activity is designed in the form of training through several stages, namely 1) coordinating with partner schools for implementation time, 2) providing material related to simple mathematics and science practicum, 3) Mentoring for Mathematics and Natural Sciences teachers in designing simple practicums, and 4) program evaluation. Participants in this activity were several Mathematics and Natural Sciences teachers from SMP N 1 Nekamese, SMP N 2 Nekamese, SMP N 4 Nekamese, and SMP N 5 Nekamese. In the training activities, the participants were quite enthusiastic in participating in the activities, which could be seen from the enthusiasm to participate in the activities and dynamic discussions. Based on the final test results, there was an increase in the teacher's ability before and after the training with an n-gain value in the high category.